A Fractional Ordered COVID-19 Model Incorporating Comorbidity and Vaccination - Meghadri Das; Guruprasad Samanta; Manuel De la Sen (Mathematics, 2021)
The primary goal of this research is to investigate COVID-19 transmission patterns in West Bengal, India in 2021; the first Coronavirus illness (COVID-19) in West Bengal was revealed on 17 March 2020. We employed the modified Susceptible-Asymptomatic-Vaccinated-Comorbidity-Infectious-Recovered (SAVICR) compartmental model as part of fractional orders because of the uncertainty created by the limited Coronavirus (COVID-19) information. In this article, two sub-compartments (Normal Infected and Infected with Co-morbidity) has been considered with vaccinated class, which is relevant in the present situation. We have studied the dynamical analysis of the system and also studied sensitivity of the parameters for West Bengal framework. We have also considered an optimal control problem taking social distancing (non-pharmaceutical treatments) as a control parameter along with vaccination.